Guardian Foster Service Program: Patterns of Handling Student Bullying Using An Ethnoparenting Approach - Wibowo, Adi; Nurmalasari, Ita (JURNAL ISLAM NUSANTARA, 2023)
This research aims to analyze the Guardian Care Service Program as a strategy for handling student bullying by implementing an ethnoparenting approach in Islamic boarding schools. Qualitative research methods were used to gain an in-depth understanding of how foster carers involve cultural values in handling bullying cases and guiding students according to the local context. Research findings show that the Foster Care Service Program is an approach that responds to cultural dynamics in Islamic boarding schools, where foster carers play a central role in creating a safe and supportive environment. This program integrates local cultural and ethical values in developing santri, creates contextual anti-bullying policies, and increases community involvement. The results of this research provide valuable insight regarding the effectiveness of the ethnoparenting approach in overcoming bullying and supporting students' positive growth in the Islamic boarding school environment. The implications of these findings can help develop similar programs in traditional Islamic educational institutions and contribute to further understanding regarding the role of foster carers and ethnoparenting approaches in creating an educational environment that is inclusive, safe, and based on local cultural values.